2009
DOI: 10.1002/ijc.24743
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic interactions govern chemically‐induced lung tumor susceptibility and Kras mutation site in murine C57BL/6J‐ChrA/J chromosome substitution strains

Abstract: Cancer susceptibility results from interactions between sensitivity and resistance alleles. We employed murine chromosome substitution strains to study how resistance alleles affected sensitive alleles during chemically-induced lung carcinogenesis. The C57BL/6J-Chr# A/J strains, constructed by selectively breeding sensitive A/J and resistant C57BL/6J (B6) mice, each contain one pair of A/J chromosomes within an otherwise B6 genome. Pas1, the major locus responsible for this differential strain response to uret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Previous attempts to inactivate Brg1 in normal lung tissue resulted in apoptosis, while in contrast, we observed that Brg1 could be successfully inactivated when lung cells had progressed to adenomas. This is thought to occur because of the frequent Kras mutations induced by ethyl carbamate administration [21, 22] that not only cause the development of adenomas but also the suppression of apoptosis [22, 23]. Hence, we then selectively inactivated (i.e., knocked out) Brg1 in the lungs of the mice through the induction of Cre recombinase via tetracycline administration (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous attempts to inactivate Brg1 in normal lung tissue resulted in apoptosis, while in contrast, we observed that Brg1 could be successfully inactivated when lung cells had progressed to adenomas. This is thought to occur because of the frequent Kras mutations induced by ethyl carbamate administration [21, 22] that not only cause the development of adenomas but also the suppression of apoptosis [22, 23]. Hence, we then selectively inactivated (i.e., knocked out) Brg1 in the lungs of the mice through the induction of Cre recombinase via tetracycline administration (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…In this model, MCA causes K-ras mutation, while BHT can promote inflammation which enhances formation of lung tumors89. The sensitivity to MCA/BHT-induced lung tumors are different among the mouse strains with an order of A/J > BABL/c > C57BL/61011. Interestingly, more MCA/BHT-induced tumors can be found in mice lacking IFN-γ expression than wild type mice which implies that the endogenous IFN-γ production may protect the animals against MCA/BHT-induced tumorigenesis23.…”
mentioning
confidence: 99%
“…A/J and cBy mice have the same sensitive Kras haplotype, so other loci presumably are responsible for generating their distinct arrays of Kras mutations. We recently showed using chromosome substitution strains that genes mapping to chromosomes other than Chr 6 influence the nature of Kras codon 61 mutations in lung tumors induced by urethane (7). …”
Section: Discussionmentioning
confidence: 99%
“…In 9 A/J and 12 cBy mice, MCA treatment was followed by 6 weekly i.p. BHT injections (150 mg/gm, week 1; 200 mg/gm thereafter), as described (6, 7). DNA was isolated from 68 A/J and 67 cBy tumors (8), an average of 4 tumors/mouse, harvested 20 wks after MCA initiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation